(untitled) (Revista Contexto & Educação, 2025)
This study analyzes the profile and characteristics of publications on “language policies and internationalization under the legacy of Paulo Freire” using a bibliometric analysis of 453 documents retrieved from Scopus (1976-2024). Data analysis was performed using Bibliometrix R package. Results indicate a growing interest in the topic, particularly after 2014, with “Paulo Freire” as the most frequent keyword. Brazil and the USA lead in publication numbers, with a strong presence of journals from various fields. Co-authorship analysis highlights the most prolific authors, while co-citation analysis reveals the influence of seminal works and research clusters. The discussion emphasizes the relevance of Freire’s ideas for promoting critical and emancipatory education within internationalization processes, advocating for South-South cooperation and decolonial perspectives. The study underscores the need for further research to deepen the understanding of language policies and internationalization from a Freirean perspective, contributing to a more just and equitable world.